HUBUNGAN OBESITAS, HIPERGLIKEMIA DAN HIPERTENSI TERHADAP SARKOPENIA PADA LANSIA DI PUSAKA KALIDERES, JAKARTA BARAT 2019-2020 - sandy Ayu Monica Silalahi; Yuda Turana; Yvonne Suzy Handajani (Bahasa Indonesia, 2021)
Introduction: Aging and physical disability are often associated with hypertension, obesity and blood sugar levels which are important factors in the development of metabolic syndrome and cardiovascular disease.This study aims to determine the relationship between obesity, hyperglycemia, hypertension and sarcopenia among the elderly at PUSAKA Kalideres, West Jakarta. Methods: This study used a cross-sectional analytical descriptive study consisting of 107 respondents aged ≥ 60 years at PUSAKA Kalideres, West Jakarta from September 2019 to November 2019. The dependent variable studied was sarcopenia, while the independent variables of the study were obesity, hyperglycemia and hypertension. The criteria for sarcopenia are based on the 2019 Asian Working Group for Sarcopenia (AWGS). Obesity is categorized if the BMI is ≥ 25 kg, hyperglycemia if the fasting blood sugar level is ≥100 mg / dL, hypertension if the blood pressure is ≥140 / 90 mmHg. Results: Based on 107 respondents, most of them were aged  65 years (62.6%) and most of them were female (70.1%). The results showed 30 respondents (28%) sarcopenia, 51 respondents (47.7%) obesity, 24 respondents (22.4%) hyperglycemia, and 31 respondents (29%) hypertension. Based on bivariate analysis, it shows that age and obesity have a significant relationship with sarcopenia p = 0.006 (p> ) and obesity p = 0.022 (p> ). The results of multivariate analysis showed that age and non-obesity were associated with sarcopenia (p = 0.005; OR = 4.734; CI = 1.587 - 14.122 and obesp = 0.015; OR = 0.309; CI = 0.120 - 0.796). Conclusion: Age is a risk factor for sarcopenia in the elderly and those who are not obese have a greater risk of developing sarcopenia.